AB0455 Clinical manifestations of vascular behçet's disease complicated with pulmonary thromboembolism. (23rd January 2014) - Kikuchi, H.; Asako, K.; Kimura, Y.; Kono, H.; Ono, Y.; Hirohata, S.
Abstract : Background: Behçet's disease (BD) is a chronic multisystemic vasculitis of unknown etiology with recurrent oral aphthous ulcers, genital ulcers, skin and ocular lesions. Serious complications may also occur in the intestinal tract, central nervous system (CNS) and vascular lesions, including ruptured aneurysms that can be a cause of death. The European League Against Rheumatism (EULAR) recommends immunosuppressive drugs for treatment of VBD to control vasculitis, but not use of antithrombotic drugs. The incidence of complication with vascular lesions is about 10% of BD in Japan, which is lower than that in the Middle East, Europe and the United States; however, antithrombotic drugs are frequently used in addition to immunosuppressive drugs because complication with deep venous thrombosis (DVT) is often found. Objectives: Clinical manifestations of vascular Behçet's disease (VBD) complicated with pulmonary thromboembolism (PTE) and treatment before and after onset were investigated, with the goal of establishment of strategies for prevention of development and recurrence of PTE. Methods: A cohort study was conducted in 43 patients with VBD who were treated in Teikyo University Hospital from 1989 to 2012. All patients fulfilling the International Study Group Criteria were evaluated. Clinical features and treatment were compared between patients with a complication of PTE and those without PTE. Results: The patients with PTE consisted of 5 males and 2 females, and had average ages of 35.0 ± 15.3 years old at the onset of BD and 38.4 ± 13.6 years old at the onset of VBD. The incidences of recurrent oral aphthous ulcers, genital ulcers and skin lesions were all 100% and those of eye involvement and epididymitis were 42.9% and 40%, respectively. The incidences of complications of intestinal, CNS and arterial lesions were all 14%. The HLA-B51 positive rates were 20% and the smoking rate was 57.1%. Three patients were treated with warfarin as anticoagulant therapy to prevent recurrence after onset of PTE. No hemorrhagic adverse reactions occurred, but the therapy was ineffective in one patient who died from recurrence (recurrence rate (RR): 33.3%). Three of the 4 patients who were not treated with warfarin had recurrence (RR: 75%) and one of these patients died due to development of a ruptured aneurysm while under immunosuppressive therapy with corticosteroids. Clinical features and treatment were compared between patients with (n=7) and without PTE (n=36). There were no significant differences in the incidence of symptoms, particular disease types, and complications. Administration of colchicine was significantly lower in the patients with PTE prior to onset of the incident. Administration of antithrombotic drugs was also significantly lower in these patients, although there was no significant difference in administration of warfarin or aspirin alone. Conclusions: Warfarin might be beneficial for secondary prevention of PTE and VBD with DVT who were not treated with warfarin had a life-threatening risk of development of this complication. PTE is a fatal complication of VBD, similarly to an arterial lesion, and further accumulation of cases and analysis in prospective studies are required to establish effective antithrombotic therapy. References: Hatemi G, et al. EULAR recommendations for the management of Behçet disease. Ann Rheum Dis. 2008;67:1656–62. Disclosure of Interest: None Declared